Artifact evaluation in information systems design science research: social constructivism environment - Ataie, Farib; Shah, Asadullah; Mior Nazri, Mior Nasir (Publications International Lahore, 2017)
Design science research methodology in information systems (IS) relates to the design, development, implementation and evaluation of artifacts solves real life problems. The iterative cycle of Design-Evaluation are an importnat requirements in this methodology. This paper describes the creation and iterative cycles of Design-Evaluation of an innovative web 2.0 based collaborative learning based on social constrcuctivism theory and Crus and Carvalho framework in Islamic education. The various qualitative and quantitative research methods are employed at various stages of study. Artifact Evaluation in Information Systems and results are described. Findings show the developed artifact could be as a good model for web 2.0 based collaborative learning, however, students should be more engaged for achieving learning goals and undoubtedly instructors's attitudes could play the main role in encouragement of students and honoring their passion and interest.